2016
DOI: 10.15406/jnhfe.2016.04.00122
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Efficacy of Infant Formula with High Sn-2 Palmitate in Formula-Fed Chinese Term Infants: an Open Label, Controlled Trial

Abstract: Objectives:We assessed the efficacy of high sn-2 palmitate infant formula as compared with breast-milk in healthy full-term Chinese infants.Methods: Seventy five term infants, aged 14 days or less, appropriate for gestational age (34 formula-fed and 41 breast-fed) were recruited to this openlabel controlled multi-center trial. Formula fed infants were assigned to receive a formula with high sn-2-palmitate (40% of the palmitic acid is esterified to the sn-2 position of the triglyceride).Results: Anthropometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…According to Carnielli et al [10], the sn-2 formula was associated with the highest fat absorption compared to other formulas. Interestingly, Zhong and his colleagues [33] showed that the high sn-2 formula had a similar effect to breastfeeding on body growth and prevention of hard stools. Béghin et al [25], reported that the sn-2 formula and standard formula had a comparable effect on the body mass; however, the sn-2 group was associated with increased bone mineral content.…”
Section: Discussionmentioning
confidence: 99%
“…According to Carnielli et al [10], the sn-2 formula was associated with the highest fat absorption compared to other formulas. Interestingly, Zhong and his colleagues [33] showed that the high sn-2 formula had a similar effect to breastfeeding on body growth and prevention of hard stools. Béghin et al [25], reported that the sn-2 formula and standard formula had a comparable effect on the body mass; however, the sn-2 group was associated with increased bone mineral content.…”
Section: Discussionmentioning
confidence: 99%